Scotch-Tape and Graphene-Oxide Photomobile Polymer Film - Riccardo Castagna; Andrea Di Donato; Rachele Castaldo; Roberto Avolio; Oriano Francescangeli; Daniele Eugenio Lucchetta (Photonics, 2022)
In this work, we report on the fabrication and photonic activation of a novel kind of photomobile polymer (PMP) film based mainly on a double layered asymmetric configuration. The PMP is cheap and extremely easy to make. It is made of PVC/isoprene tape with a layer of graphene-oxide (GO) attached. Under illumination at different intensities, and with coherent and incoherent light sources, the bending of the PMP film changes considerably. In particular, we noticed a more efficient bending effect when the film is directly exposed to high light intensities or to NIR radiation in the case of incoherent light sources. For the exposure times used in our experiments, the process is completely reversible when the light source is switched off. Additionally, if we paint the side of the PVC tape exposed to light black, the film is not able to return to its starting position and the bending results are permanent. This suggests that the presence of the GO-layer is responsible for the restoration of the position of the PMP film.